Electrical conductivity of doped porous glasses as possible sensors for oxygen - Saraidarov, Tsiala; Reisfeld, Renata; Zigansky, Elena; Sashchiuk, Aldona; Lifshitz, Efrat (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
We are proposing Rubpy complex incorporated in a number of porous sol–gel thin films as a sensor for oxygen. The principle is based on the following fact: triplet oxygen reacts with the excited states of Rubpy resulting in decay of luminescence of the complex due to triplet quenching. The decrease of fluorescence is proportional to the amount of absorbed oxygen. We discuss here several sol–gel matrices with doped by Ru(bpy)3+2 deposited as thin films on ITO conducting glass. The absorption and emission spectra of the complex, and electrical conductivity of the doped films show how the fluorescence can be excited either by optical or electronic means. The decrease of fluorescence indicates the concentration of oxygen.
Optica Applicata, Vol. 38, 2008, nr 1, s. 109-117
Keywords: optyka; Rubpy complex; porous glasses; sensors for oxygen; fluorescence; electrical conductivity